Agama dan Keamanan - Semy Arayunedya (Reformed Center for Religion and Society, 2021)
The change in the security paradigm still remains an opportunity for religions to make the bargaining power of ideas about world’s affairs. People and religion institutions should participate and contribute on exact science to the humanities from the present range to the future. Certainly, it doesn't just stop when we work hard to help natural disasters victims, overcoming poverty, uphold human rights, or fight for a decent living environment, and the universal mission of religion but also to focus on human flourishing. This mission can only be accomplished by turning from the love of pleasure, which is the main axis of today's culture, to the pleasure of love.